2019
DOI: 10.18817/repesca.v12i1.1682
|View full text |Cite
|
Sign up to set email alerts
|

Riscos Ocupacionais E Medidas De Prote��o Dos Trabalhadores Identificados Em Uma Piscicultura No Munic�pio De Santa Rita-Ma

Abstract: Resumo -Os trabalhadores da piscicultura executam suas atividades laborais diárias em ambiente com exposição a riscos ocupacionais, que afetam o desempenho laboral e a saúde do profissional. Nessa perspectiva, é necessária a identificação desses riscos e o estabelecimento de medidas de segurança para garantir um ambiente seguro, assim como promover a saúde dos trabalhadores da piscicultura. Este trabalho teve como objetivo avaliar os riscos ocupacionais e as medidas de proteção dos trabalhadores identificados … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
1
0
3
Order By: Relevance
“…The absence of low back pain was reported by 50% of the IG participants at the end of the treatment, whereas in the CG, 100% of the professionals had low back pain during data collection (T0, T1, and T2). A study on occupational risks conducted in the state of Maranhão showed that low back pain is an important ergonomic risk 30 . Specifically, among professionals of a prison in Florianópolis (SC), low back pain was mentioned as a pathological condition associated with the occupational activity 31 .…”
Section: Discussionmentioning
confidence: 99%
“…The absence of low back pain was reported by 50% of the IG participants at the end of the treatment, whereas in the CG, 100% of the professionals had low back pain during data collection (T0, T1, and T2). A study on occupational risks conducted in the state of Maranhão showed that low back pain is an important ergonomic risk 30 . Specifically, among professionals of a prison in Florianópolis (SC), low back pain was mentioned as a pathological condition associated with the occupational activity 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Apesar da sua importância, poucos estudos foram realizados no sentido de compreender o comportamento da radiação no Brasil (Medeiros, 2018;Penereiro, 2017;Frazão et al, 2019;Kozmhinsky et al, 2018;, dentre as dificuldades encontradas está a extensão territorial do país que aumenta o custo para medição (FUNARI, 2017).…”
Section: Introductionunclassified
“…Apesar da sua importância, poucos estudos foram realizados no sentido de compreender o comportamento da radiação no Brasil (MEDEIROS, 2018;PENEREIRO, 2017;FRAZÃO et al, 2019;KOZMHINSKY et al, 2018;SILVA et al, 2018 ), dentre as dificuldades encontradas está a extensão territorial do país que aumenta o custo para medição (FUNARI, 2017).…”
Section: Introductionunclassified